PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Tanjung, Irmanisa Ikhwani; Hendrian, Hendrian; Geraldina, Ira (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
This study aims to determine the effect of intellectual capital and good corporate governance on firm value with financial distress as intervening variable. This quantitative study use secondary data on banking companies listed on the Indonesia Stock Exchange (IDX). The sample of this study was 117 banks listed on the IDX for the 2019-2021 period and was analyzed using Eviews 12. The results of this study is intellectual capital has positive effect on firm value, intellectual capital has negative effect on financial distress, good corporate governance has no effect on firm value and financial distress. In addition, intellectual capital has effect on firm value through financial distress as intervening variable, and good corporate governance has no effect on firm value through financial distress as intervening variable during the Covid-19 pandemic.